DENSITY OF FABRIC YARN IN MULTI-LAYER FABRICS - Kosimov Azamjon Adikhamjonovich (World Scientific Research Journal, 2025)
Abstract. In the given work formation of fabrics on a weaving loom influences of linear durability of filling yarn on refueling tension and a number of other parameters is investigated.